Bioactive Properties of Venoms Isolated from Whiptail Stingrays and the Search for Molecular Mechanisms and Targets - Craig A. Doupnik; Carl A. Luer; Catherine J. Walsh; Jessica Restivo; Jacqueline Xinlan Brick (MDPI AG, 2024)
The venom-containing barb attached to their 'whip-like' tail provides stingrays a defensive mechanism for evading predators such as sharks. From human encounters, dermal stingray envenomation is characterized by intense pain often followed by tissue necrosis occurring over several days to weeks. The bioactive components in stingray venoms (SRVs) and their molecular targets and mechanisms that mediate these complex responses are not well understood. Given the utility of venom-derived proteins from other venomous species for biomedical and pharmaceutical applications, we set out to characterize the bioactivity of SRV extracts from three local species that belong to the Dasyatoidea 'whiptail' superfamily. Multiple cell-based assays were used to quantify and compare the in vitro effects of these SRVs on different cell lines. All three SRVs demonstrated concentration-dependent growth-inhibitory effects on three different human cell lines tested. In contrast, a mouse fibrosarcoma cell line was markedly resistant to all three SRVs, indicating the molecular target(s) for mediating the SRV effects are not expressed on these cells. The multifunctional SRV responses were characterized by an acute disruption of cell adhesion leading to apoptosis. These findings aim to guide future investigations of individual SRV proteins and their molecular targets for potential use in biomedical applications.